Muon studies of molecular magnetism - Blundell, S; Husmann, A; Jestadt, T; Pratt, F; Marshall, I; Lovett, B; Kurmoo, M; Sugano, T; Hayes, W (Elsevier, 2000)
We present the results of mu SR experiments on a variety of molecular magnetic materials, either purely organic or combinations of transition metal ions and organic groups, which have been recently prepared. In a purely organic metamagnet, tanol suberate, we have observed a spin precession signal with a temperature dependence which has provided evidence of the two-dimensional nature of the antiferromagnetic ground state. In a family of dicyanamide-based molecular magnets with ordering temperatures of up to 21 K, and in a ferrimagnetic cobalt hydroxide, mu SR has been used to study the temperature dependence of the spin fluctuations. (C) 2000 Elsevier Science B.V. All rights reserved.